State and Trends of Carbon Pricing 2016 - World Bank; Ecofys; Vivid Economics (Washington, DC: World Bank, 2016)
This report provides an up-to-date overview of existing and emerging carbon pricing instruments around the world, including national and subnational initiatives. Furthermore, it gives an overview of current corporate carbon pricing initiatives. Another key focus of the report is on the importance of aligning carbon pricing with the broader policy landscape. The analysis provides lessons for policymakers on how maximize synergies between climate mitigation and other related policies, while managing potential tensions and tradeoffs. It also provides new modelling analysis to demonstrate the crucial benefits that an international carbon market established under Article 6 of the Paris Agreement could provide in reducing the costs to countries of achieving their emission reduction targets. An international carbon market could thus enable greater ambition in taking steps to reduce greenhouse gas emissions to a level consistent with the 2°C climate stabilization goal.